OBITUARY: Bravo Raja Sahib (1923-2010) - Mirza, Dil Muhammad (Pakistan Journal of Ophthalmology, 2010)
OBITUARY Bravo Raja Sahib (1923-2010) On Friday May 7th 2010 Raja Mumtaz Quli Khan passed away peacefully at his home in Lahore. Physically debilitated but mentally active and alert till his death. His death is most acutely felt by his family but poignantly experienced by all with whom he was associated as he was deeply admired by his students, patients, colleagues and friends. In him we have lost a giant in ophthalmology and the father of Ophthalmological Society of Pakistan. His sad demise marks the end of an era.